2021
DOI: 10.1007/s10072-021-05467-w
|View full text |Cite
|
Sign up to set email alerts
|

A case of acute demyelinating polyradiculoneuropathy with bilateral facial palsy after ChAdOx1 nCoV-19 vaccine

Abstract: Background The coronavirus disease 2019 global pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), began in late 2019. Researchers around the world are aggressively working to develop a vaccine. One of the vaccines approved against COVID-19 is Oxford-AstraZeneca chimpanzee adenovirus vectored vaccine ChAdOx1 nCoV-19. Case report We described a patient who developed four limb distal paraesthesia, postural instability, and facial diplegia, ten days after vaccination with ChAdOx1 nC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…Nasuelli et al has reported a case of acute demyelinating polyradiculoneuropathy with bilateral facial palsy after AstraZeneca chimpanzee adenovirus vectored vaccine ChAdOx1 nCoV-19 vaccine. 6 The two patients we report here were of similar ages and presented within 1 week of each other, this may be a result of the age-specific vaccination scheme in the UK.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Nasuelli et al has reported a case of acute demyelinating polyradiculoneuropathy with bilateral facial palsy after AstraZeneca chimpanzee adenovirus vectored vaccine ChAdOx1 nCoV-19 vaccine. 6 The two patients we report here were of similar ages and presented within 1 week of each other, this may be a result of the age-specific vaccination scheme in the UK.…”
Section: Discussionmentioning
confidence: 57%
“…Nasuelli et al has reported a case of acute demyelinating polyradiculoneuropathy with bilateral facial palsy after AstraZeneca chimpanzee adenovirus vectored vaccine ChAdOx1 nCoV-19 vaccine. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of GBS have been reported after both ChAdOx1 or BNT162b2. [2225] In the U.S, 78 cases of GBS have been reported after the use of the adenoviral vector vaccine from Janssen, with a reported frequency of 7.8 cases per million doses,[26] similar to the 6.3 reports per million doses with ChAdOx1, which like the Janssen vaccine is also an adenoviral vector vaccine. Damage to axonal or myelin membranes mediated directly by vaccine virus or vaccine-associated products and cross-reactivity with epitopes on myelin or axonal glycoproteins of peripheral nerves, have been cited as potential mechanisms behind GBS following the administration of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Instances of these and other neuro-immune events also have been reported elsewhere. Reports after ChAdOx1 include seven cases of GBS in India, [7] two in the UK, [8,9] one in each of in France, [10] Italy, [11] and Malta, [12] and nine cases of bifacial weakness with paresthesias, a variant of GBS, in the UK, [13,14] and one in Italy, [15] and two cases of sensory GBS in Korea. [16] Three cases of acute transverse myelitis were reported during the clinical trials for ChAdOx1, [17,18] two in case studies, [19,20] and one report of longitudinal extensive transverse myelitis after ChAdOx1 vaccination reported in a case study.…”
Section: Main Text [3177words] Introductionmentioning
confidence: 99%